2018
DOI: 10.3390/beverages4030047
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and Pitfalls on the Use of Passion Fruit By-Products in Drinkable Yogurt: Physicochemical, Technological, Microbiological, and Sensory Aspects

Abstract: Peels and seeds are the primary by-products of the passion fruit agroindustry. This study was designed to evaluate the potential of passion fruit peel and seeds flour (PFF) as a source of fiber and minerals to enhance the functional properties of drinkable yogurt. Proximate composition, mineral content, technological (pH, viscosity, color, and syneresis), and microbiological analyses (lactic acid bacteria, as well as yeast and mold counts), acceptance test, descriptive sensory analysis, and shelf life assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…Thus, it is frequently recommended to consume whole foods and eat certain fruits with their peels. These peels and other processing by-products are not only rich sources of dietary fibre and minerals [ 33 , 34 , 35 , 36 ], but are also important sources of phenolic compounds [ 25 , 37 , 38 ]. Various phenolic compounds, such as phenolic acids and flavonoids, are present in many seeds, particularly in their hulls or seed coats [ 39 ].…”
Section: Role Of Genetics On the Distribution And Biosynthesis Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is frequently recommended to consume whole foods and eat certain fruits with their peels. These peels and other processing by-products are not only rich sources of dietary fibre and minerals [ 33 , 34 , 35 , 36 ], but are also important sources of phenolic compounds [ 25 , 37 , 38 ]. Various phenolic compounds, such as phenolic acids and flavonoids, are present in many seeds, particularly in their hulls or seed coats [ 39 ].…”
Section: Role Of Genetics On the Distribution And Biosynthesis Of mentioning
confidence: 99%
“…Although peanut skin is used as an example here, the same concept may be extended to different plant food by-products, especially those generated from processing of certain fruits, nuts, grains, seeds, and other non-perishable food, for which storage conditions may not be adequately considered by the producers and the industry. According to Toledo et al [ 36 ], the addition of passion fruit peel and seed flour increased the growth of yeast and mold in a food model system. Brazil nut skin and hard shell, by-products of the cracking and shelling process, have also been regarded as potential sources of bioactive compounds [ 80 ], but their safety requires attention.…”
Section: Microbiological Safety and Decontaminationmentioning
confidence: 99%
“…Several studies have demonstrated that color, an important parameter influencing consumers' decision, should be investigated in novel food products, as well as during food processing and long-term storage (da Silva et al, 2014;de Toledo et al, 2018;Selani et al, 2016). Therefore, the color of fillets subjected to smoking was measured for three different parts of the salmon, namely, outside and middle portion as well as the skin (Table 3) Furthermore, such minor differences, with exception of the lightness (outside portion), disappeared during storage.…”
Section: Color Effects In Smoked Salmonmentioning
confidence: 99%
“…Several tropical and subtropical fruit pulps are used for the production of fermented dairy beverages in Latin America, e.g., guava, soursop (Annona muricata L.), mango, umbu (Spondias tuberosa Arruda), strawberry and peach [99]. More examples of by-product repurposing include beverages prepared with passion fruit [100], i.e., fermented milk, and drinkable yogurts using peel [101][102][103], and peel and seed flour [104]. Later on, it will be evident that fruits can be a source of mycotoxin contamination which may very well reach final products [6].…”
Section: Fermented Beveragesmentioning
confidence: 99%